Guide to Qualitative Research in Parliaments Experiences and Practices - Berthet, Valentine (Springer Nature, 2023)
This open access book is a hands-on guide on doing qualitative research in parliaments, exploring achievements and drawbacks for all. From early-career scholars looking for an 'in' to start their research to senior academics interested in methodological details, the book offers a novel approach to discussing qualitative methodologies. It presents unique insights based on a large-scale qualitative study in the European Parliament using interview and ethnographic data. Comprehensive yet accessible, the book accounts the step-by-step process of qualitative research in parliaments, offering a reflexive and analytical perspective that moves beyond a textbook or theory-only format.